1996
DOI: 10.1128/mcb.16.5.2473
|View full text |Cite
|
Sign up to set email alerts
|

Functional Regions of the Mouse Thrombopoietin Receptor Cytoplasmic Domain: Evidence for a Critical Region Which Is Involved in Differentiation and Can Be Complemented by Erythropoietin

Abstract: Thrombopoietin (TPO) is the major regulator of growth and differentiation of megakaryocytes. To identify functionally important regions in the cytoplasmic domain of the TPO receptor, mpl, we introduced wild-type mpl and deletion mutants of murine mpl into the granulocyte-macrophage colony-stimulating factor (GM-CSF)-or erythropoietin (EPO)-dependent human cell line UT7. TPO induced differentiation of UT7-Wtmpl cells, not parental UT7 cells, along the megakaryocytic lineage, as evidenced by decreased proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
96
1

Year Published

1996
1996
2000
2000

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(104 citation statements)
references
References 48 publications
7
96
1
Order By: Relevance
“…Because of the restricted expression of the TPO receptor c-Mpl in megakaryoblastic cells [45], experiments were carried out using the UT7-Mpl cell line expressing the murine c-Mpl. TPO treatment of these cells has been shown to induce increased levels of specific megakaryocytic differentiation antigens and to reduce those of erythroid markers [46,47]. Control and TPO-treated UT7-Mpl cell lysates were tested for their expression of GPIIIa, SERCAs and calreticulin as in Figure 1 expression level of SERCA3 was also observed under physiologically induced megakaryocytic differentiation.…”
Section: Co-regulation Of the Expression Of Serca3 And Gpiiia Upon Tpmentioning
confidence: 99%
“…Because of the restricted expression of the TPO receptor c-Mpl in megakaryoblastic cells [45], experiments were carried out using the UT7-Mpl cell line expressing the murine c-Mpl. TPO treatment of these cells has been shown to induce increased levels of specific megakaryocytic differentiation antigens and to reduce those of erythroid markers [46,47]. Control and TPO-treated UT7-Mpl cell lysates were tested for their expression of GPIIIa, SERCAs and calreticulin as in Figure 1 expression level of SERCA3 was also observed under physiologically induced megakaryocytic differentiation.…”
Section: Co-regulation Of the Expression Of Serca3 And Gpiiia Upon Tpmentioning
confidence: 99%
“…Our finding that the minimal domain of EpoR able to support differentiation is the same as that required to support cell proliferation raises the possibility that the role of the EpoR-activated signals is only to support the survival and proliferation of the differentiating progenitors, as proposed by the stochastic hypothesis. It is possible, however, by analogy with studies on the granulocyte-colony-stimulating factor or thrombopoietin receptors (44,45), that, to support erythroid gene expression, additional signals are needed beyond those required for proliferation. If this is the case, these signals must arise from the membrane-proximal domain of the EpoR and cannot be unique to the EpoR.…”
Section: Wild-type Prlr Can Fully Support Differentiation Of Erythroimentioning
confidence: 99%
“…33,34 Previous studies have shown that UT-7, a growth factordependent cell line established from a patient with acute megakaryoblastic leukemia, 35 represents a useful in vitro model to study megakaryocytopoiesis. [36][37][38][39][40] Particularly, UT-7 TPO and UT-7 GM 38 sublines undergo megakaryocytic differentiation following incubation with Tpo. UT-7 cells have many similarities with TF-1 cells.…”
Section: Discussionmentioning
confidence: 99%